Top Management Team Power in China: Measurement and Validation - Ke, Bin; Mao, Xinshu; Wang, Bin; Zuo, Luo (Management Science, 2021)
We propose and validate a comprehensive measure of power for the top management teams (TMTs) of publicly listed Chinese firms. We show that our measure is positively associated with the four power dimensions developed by prior research for U.S. firms as well as three Asia-relevant power dimensions, including political capital, seniority, and gender. We find that our TMT power measure is a valid proxy for TMT power for both state-controlled firms and non-state-controlled firms. We also compare our TMT power measure with one alternative TMT power proxy based on executive compensation and find no evidence that the alternative proxy is better than our measure in capturing TMT’s true power. Further, we provide evidence that the divergence between our power proxy and the power proxy based on executive compensation reflects nonmarket institutional forces in China and has important implications for corporate outcomes. This paper was accepted by Brian Bushee, accounting.